Forensic Dermatology Expert Analytical Report: A New Frontier of Forensic Medicine - Philip R. Cohen; Lerah Sutton (Dermatology and Therapy)
Abstract Specialists in forensic medicine assist in crime scene investigations. The forensic medicine experts include anthropologists, ballistic analysts, entomologists, odontologists, and osteologists. The experts are usually not at the crime scene; they provide an evaluation of evidence that is sent to them. After they complete their assessment of the evidence, they prepare a specialized presentation of their findings: a forensic expert analytical report. The format of the report is variable depending on which forensic expert is writing it; however, there are certain mandatory sections that are included: the chain of evidence, the methods of evidence evaluation, the results of the evaluation of the evidence, and the discussion (including the conclusion) of what the evidence demonstrates. Forensic dermatology is an emerging subfield of medicine. Dermatologists are experts in evaluating the skin, mucosa, hair, and nails. It is anticipated that the demand for forensic dermatology will increase as individuals who currently evaluate crime scenes become aware of the potential benefit of consulting a forensic dermatologist. An illustrative hypothetical forensic dermatology expert analytical report is presented. Like other forensic expert analytical reports, the forensic dermatology expert analytical report has four primary sections. The chain of evidence section is a chronologic documentation that not only identifies the protected care and control of the evidence but also the transfer of the evidence to another individual. The methods section is a comprehensive presentation of the analysis of the evidence; it comprises the majority of an analytical report. The results section provides the information obtained after the evidence has been evaluated; it should be written in plain language, so it is readily able to be understood by not only the other investigators but also the members of the legal profession (including the judge and the attorneys) and the members of the jury. The discussion section includes the opinion of the dermatologist and should be a summary of the investigation findings that puts the analysis of the evidence into context; it can include a conclusion section and should also be written in plain language. Depending on the specific circumstances of the case, the template of the illustrative forensic dermatology expert analytical report can be modified by the dermatologists who is preparing their analytical report. In conclusion, an excellent forensic dermatology expert report will aid both other investigators and the members of the legal system—such as the attorneys, judge, and jury—who are involved in the case. In addition, when the forensic dermatology expert testifies as an expert witness in court, the report will be an asset for the dermatologist.